Curcumin protects radiation-induced liver damage in rats through the NF-κB signaling pathway - Wei Li; Liangjun Jiang; Xianzhou Lu; Xianrong Liu; Mingjiong Ling (BMC Complementary Medicine and Therapies, 2021)
Abstract Background Curcumin has been demonstrated to exert anti-oxidant, anti-fibrotic, anti-inflammatory, and anti-cancer activities. This study was conducted to observe the effect and inner mechanism of curcumin in rats with radiation-induced liver damage (RILD). Methods Thirty SD rats were classified into Control, Radiation group and Curcumin (Cur) + Radiation group (n = 10 in each group). The changes in body weight of the rats were observed on the 3rd, 7th and 14th days after the treatment with curcumin. On the 14th day post treatment, the heart blood of the rats was drawn for measurement of liver function indices including total protein (TP), alanine aminotransfetase (ALT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) as well as aspartate aminotransfetase (AST). Subsequently, the rats were euthanized and liver tissues were taken to observe liver morphological changes using hematoxylin-eosin (HE), and to analyze apoptosis condition using transferase-mediated deoxyuridine triphosphate-biotin nick end labeling (TUNEL) assays. Meanwhile, the oxidative stress level in liver tissue homogenate was determined by biochemical analysis. The expression of nuclear factor kappa B (NF-κB) pathway-associated and apoptosis-associated proteins was detected using Western blot analysis, and the expression levels of inflammatory factors were measured by Enzyme-linked immunosorbent assay (ELISA). Results The reduced body weight was observed in rats of the Radiation group compared to the Control and Cur + Radiation groups on day 14. In the Radiation group, hepatic cell edema and inflammatory cell infiltration could be visible under the light microscope, and the hepatocytes presented with vacuolar degeneration. In the Cur + Radiation group, the hepatocytes swelled under the microscope, but the pathological changes were alleviated in comparison with the Radiation group. RILD rats with curcumin treatment presented with decreased ALT, AST, ALP, LDH, and maleicdialdehyde (MDA) levels, and elevated TP, superoxide dismutase (SOD), caspase activated DNase (CAD) and glutathione (GSH) levels. Apoptosis and inflammation in rats with RILD were up-regulated, and the NF-κB pathway was activated, but they were reversed after continuously intragastric administration of curcumin for 14 days. Conclusion Our study highlights that curcumin treatment reduces the liver damage caused by radiation through the inhibition of the NF-κB pathway.